Correlation of Exceeding of Speed Limits and Traffic Accidents in Hungary - Mészáros, Gábor (Magyar Rendészet, 2018)
Road traffic safety is a high priority issue in Hungary and in the European Union. Accident prevention programmes aim to reduce the number of fatalities in road accidents. To examine the effectiveness of the programmes it is inevitable to create a database in connection with accidents and a network of information with the analysis and the representation of the data. The essay aims to review the information processes involved in the road traffic accident prevention system and the analysis of the disorders in the system with the utilization of the principles of military Information Operations.